Reaction of a 2, 4, 6-triphenylphosphinine ferrate anion with electrophiles: a new route to phosphacyclohexadienyl complexes. Issue 21 (6th May 2016) - Hoidn, Christian M.; Wolf, Robert
Abstract : Electrophilic attack at π-coordinated 2, 4, 6-triphenylphosphinine afforded a range of novel complexes with substituted η 5 -phosphacyclohexadienyl ligands. Abstract : A novel, versatile route to phosphorus- and carbon-substituted η 5 -phosphacyclohexadienyl complexes was developed. Reaction of the anionic 2, 4, 6-triphenylphosphinine iron complex [K([18]crown-6)(thf)2 ][Cp*Fe(PC5 Ph3 H2 )] (1 ) with selected main group element electrophiles afforded the new complexes [Cp*Fe(2- endo -H-PC5 Ph3 H2 )] ( endo -3 ), [Cp*Fe(2- exo -H-PC5 Ph3 H2 )] ( exo -3 ), [Cp*Fe(1-Me-PC5 Ph3 H2 )] (4 ), [Cp*Fe(1-Me3 Si-PC5 Ph3 H2 )] (5 ), [Cp*Fe(1-PPh2 -PC5 Ph3 H2 )] (6 ) and [Cp*Fe(2-BCat-PC5 Ph3 H2 )] (7, BCat = 2-benzo[ d ][1, 3, 2]dioxaborol-2-yl). Initial attack of the electrophile at phosphorus was observed, leading to a P-substitued phosphinine ligand. A subsequent rearragement occured in some cases, resulting in C-substituted phosphinine complexes endo -3, exo -3 and7 . The new complexes were characterized by 1 H, 31 P{ 1 H}, and 13 C{ 1 H} NMR spectroscopy, UV-vis spectroscopy and elemental analysis; their molecular structures were determined by X-ray crystallography.